Nanocellulose: Beyond the Ordinary - Kojiro Uetani; Takuya Kitaoka (BioResources, 2020)
Nanocellulose is a collective term for nanoassemblies of macromolecular cellulose in fibrous and crystalline forms, mainly originating from woody bioresources. Fascinating physicochemical properties of nanocellulose, such as high strength, light weight, transparency, and low thermal expansion, have allowed development of nanocellulose-based functional materials, but most of these materials face serious competition from existing products. The inherent nanoarchitectures of nanocellulose cannot be reconstructed by artificial means, and they are expected to contain unknown functions that have not yet been achieved. Nanocellulose can “run its own show” in the forthcoming sustainable society through determining and highlighting its nanostructure-triggered novel material functions that are beyond the ordinary.